Semiotic analysis of English books of Punjab Textbook Board (Pakistan) with Gender Lens: Exploring the gender sensitization level of Punjab Textbook Board officers - Tahira Akbar, Ra’ana Malik, (PJE, 2023)
Semiotics is visual literacy which is an important aspect of learning process involving various social aspects of a society. Visuals are used dominantly in all books of early learners because it is considered the most efficient way of learning and teaching. Representation of gender through visual literacy is the most current and debatable social issue in the contemporary world.